Why performing arts belongs in the school of life - Adams, Paul (Institutional Knowledge at Singapore Management University, 2019)
I’ve been involved in the performing arts almost all my life—whether I was playing a rock- and-roll shepherd in my primary school’s Nativity production, or in my current role as the Learning and Engagement Manager for the Singapore Repertory Theatre (SRT).